Analysis of goal scoring in European elite soccer teams - Santos, F.; Belchior, D.; Mendes, B.; Mauricio, N.; Furtado, B.; Sousa, P. M.; Pinheiro, V. (Journal of Sport Pedagogy and Research, 2018)
The study aimed to analyze the situations of game that resulted in a goal, from ball recovery to finalization, using the notational and sequential analysis. We observed 236 goals - seniors` A (n=86), seniors` B (n=81) and juniors` A (n=69). For the coding of the goals we use the observational instrument SOGF and the program LINCE®. Data processing was performed using IBM SPSS Statistics® and SDIS-GSEQ®. Some regularities were detected in the teams observed. We record more instances for the goals in which the recovery of the ball results from fouls suffered, in the zones of the half offensive field, in which the last pass is executed in the offensive zones and the finalization inside the area, with the right foot. The most effective method of play is the positional attack. The tactical schemes are also of great importance for the goal. The use of quantitative and qualitative analysis techniques allows to collect a set of important information for the professional activity of the coaches.